Impaired neurogenesis and neural progenitor fate choice in a human stem cell model of SETBP1 disorder - Lucia F. Cardo; Daniel C. de la Fuente; Meng Li (Molecular Autism, 2023)
Abstract Background Disruptions of SETBP1 (SET binding protein 1) on 18q12.3 by heterozygous gene deletion or loss-of-function variants cause SETBP1 disorder. Clinical features are frequently associated with moderate to severe intellectual disability, autistic traits and speech and motor delays. Despite the association of SETBP1 with neurodevelopmental disorders, little is known about its role in brain development. Methods Using CRISPR/Cas9 genome editing technology, we generated a SETBP1 deletion model in human embryonic stem cells (hESCs) and examined the effects of SETBP1-deficiency in neural progenitors (NPCs) and neurons derived from these stem cells using a battery of cellular assays, genome-wide transcriptomic profiling and drug-based phenotypic rescue. Results Neural induction occurred efficiently in all SETBP1 deletion models as indicated by uniform transition into neural rosettes. However, SETBP1-deficient NPCs exhibited an extended proliferative window and a decrease in neurogenesis coupled with a deficiency in their ability to acquire ventral forebrain fate. Genome-wide transcriptome profiling and protein biochemical analysis revealed enhanced activation of Wnt/β-catenin signaling in SETBP1 deleted cells. Crucially, treatment of the SETBP1-deficient NPCs with a small molecule Wnt inhibitor XAV939 restored hyper canonical β-catenin activity and restored both cortical and MGE neuronal differentiation. Limitations The current study is based on analysis of isogenic hESC lines with genome-edited SETBP1 deletion and further studies would benefit from the use of patient-derived iPSC lines that may harbor additional genetic risk that aggravate brain pathology of SETBP1 disorder. Conclusions We identified an important role for SETBP1 in controlling forebrain progenitor expansion and neurogenic differentiation. Our study establishes a novel regulatory link between SETBP1 and Wnt/β-catenin signaling during human cortical neurogenesis and provides mechanistic insights into structural abnormalities and potential therapeutic avenues for SETBP1 disorder.